Social Exchange Relationship and Employee Attitudes toward Newly Introduced Information System - Chou, Paul (European Scientific Journal, ESJ, 2016)
Almost all organizations in the world are under pressure to adopt new information systems in order to survive in competitive markets. Thus, improving our understanding of the inner working mechanism associated with adoption of new information systems has become increasingly important for researchers and practitioners alike. Although Davis’ technology acceptance model is the most widely applied theory, very little effort has been devoted to understanding the determinants of new system acceptance and usage beyond Davis’ model. In view of such, the main aim of this study is to investigate the driving force behind acceptance of and intent to use new information systems from the perspective of social exchange relationship. Results obtained confirm that perceived organizational support and leader-member exchange exert their influences via affective commitment to organization on attitude towards newly introduced information system. Practical implications, contributions and limitations of this study are discussed with suggestions for future research proposed.